2015
DOI: 10.1111/nph.13680
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomics investigation into pine reproductive organ development

Abstract: SummaryThe development of reproductive structures in gymnosperms is still poorly studied because of a lack of genomic information and useful genetic tools. The hermaphroditic reproductive structure derived from unisexual gymnosperms is an even less studied aspect of seed plant evolution.To extend our understanding of the molecular mechanism of hermaphroditism and the determination of sexual identity of conifer reproductive structures in general, unisexual and bisexual cones from Pinus tabuliformis were profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 65 publications
3
41
0
Order By: Relevance
“…Likewise, SOC1 and SOC1‐like annotated P. glauca genes, WS0056_A03 and WS00922_C06, respectively, are homologs of P. abies DAL3 (PaMADS7_DAL3; Melzer et al ., ). Functional analysis of CjMADS14 , the Cryptomeria japonica ortholog of P. abies DAL1 , and CjMADS15 , the C. japonica ortholog of P. abies DAL3 , indicated that expression of DAL1 is specific to the reproductive organs (and its function is related to suppressing reproductive repressors), whereas expression of DAL3 is more ubiquitous but included male and female strobili (Katahata et al ., ; Niu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, SOC1 and SOC1‐like annotated P. glauca genes, WS0056_A03 and WS00922_C06, respectively, are homologs of P. abies DAL3 (PaMADS7_DAL3; Melzer et al ., ). Functional analysis of CjMADS14 , the Cryptomeria japonica ortholog of P. abies DAL1 , and CjMADS15 , the C. japonica ortholog of P. abies DAL3 , indicated that expression of DAL1 is specific to the reproductive organs (and its function is related to suppressing reproductive repressors), whereas expression of DAL3 is more ubiquitous but included male and female strobili (Katahata et al ., ; Niu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al (2001Wang et al ( , 2004, Li et al (2008), and Zhang and Liu (2015) conducted partial studies on the external morphological, reproductive and reproductive biology characteristics of P. massoniana polycone. Niu et al (2016) studied the gene expression of the unisexual and heterotypic bisexual flowers on polycone type P. tabuliformis. Using the male flowers which were gradually changing into the female flowers as experimental material, they found that the transcription of the male flower part of the bisexual flower was more similar to the normal female flower.…”
Section: Discussionmentioning
confidence: 99%
“…Franco (Pullman et al, 2005), Pinus tabuliformis Carr. (Niu et al, 2013(Niu et al, , 2016; Pinus thunbergii Parl. (Kong et al, 2012), Pinus bungeana Zucc.…”
Section: Introductionmentioning
confidence: 99%
“…Yet until now few studies have focused on the development of Pinus reproductive organs. In Pinus tabuliformis, unusual bisexual cones were found; here, the gene expression pattern of MADS-box transcription factors, FT/TFL1-like and LFY/NDLY genes was compared between unisexual and bisexual cones [52]. In Pinus bungeana, 39.62 Gb of RNA sequencing data was analyzed from two kinds of sexual cones, obtaining 85,305 unigenes, 53,944 (63.23%) of which were annotated in public databases [53].…”
Section: Gymnosperm Gene Annotation Using Transcriptome Datamentioning
confidence: 99%